Parents and grandparents of deaf children in Ecuador: concerns and expectations. Issue 10 (26th November 2017) - Huiracocha-Tutiven, Lourdes; Orellana-Paucar, Adriana; Brito, Liliana; Blume, Stuart
Abstract: Despite a growing number of anthropological studies of deaf communities, little attention has been paid to how socioeconomic and cultural factors influence the experiences and the concerns of hearing parents of deaf and hearing-impaired (DHI) children. This study draws on interviews with parents (and some grandparents) of DHI children in Ecuador, a country marked by profound inequality but also by considerable recent progress in poverty reduction and enhanced provisions for people with disabilities. Despite progress, many carers are nevertheless critical of the way in which new measures have been implemented, and of the schooling available to their child. They are also worried by their child's vulnerability, the likelihood of discrimination, and the possibility of abuse.